2005
DOI: 10.1183/09031936.05.00080804
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan therapy for portopulmonary hypertension

Abstract: The dual endothelin receptor antagonist bosentan has been approved in several countries for pulmonary arterial hypertension, and patients with portopulmonary hypertension (PPHTN) have not specifically been excluded. However, no data have been published on the efficacy and safety of bosentan in this patient population. Here, the first clinical experiences with bosentan in patients with Child A cirrhosis and severe PPHTN are reported.In total, 11 consecutive patients with cirrhosis and severe PPHTN in New York H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
111
1
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(126 citation statements)
references
References 33 publications
6
111
1
8
Order By: Relevance
“…In the current retrospective study, a significant clinical, functional and haemodynamic improvement was found over 3 months' treatment with oral sildenafil in patients with severe POPH. Successful treatment of POPH has been reported using prostanoids or endothelin-receptor antagonists, with observation times of 3-12 months [9][10][11][12][13]. Subcutaneous, i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current retrospective study, a significant clinical, functional and haemodynamic improvement was found over 3 months' treatment with oral sildenafil in patients with severe POPH. Successful treatment of POPH has been reported using prostanoids or endothelin-receptor antagonists, with observation times of 3-12 months [9][10][11][12][13]. Subcutaneous, i.v.…”
Section: Discussionmentioning
confidence: 99%
“…So far, case reports and a case series have been published showing clinical, functional and haemodynamic benefit on treatment with intravenous and inhaled prostanoids, oral bosentan or combination therapy [9][10][11][12][13].…”
mentioning
confidence: 99%
“…Conventional treatment consists of fluid overload with diuretics and oxygen but does not improve survival rate [15]. Inhibitors of 1-endothelin as bosentan are an effective treatment in stable hepatic illness, however there is insufficient evidence of its effectiveness in patients with altered hepatic dysfunction [16]. Furthermore, patients treated with bosentan have shown better results in hemodynamic parameters and the 6 minute-walk distance test (6MWD) compared with patients treated with inhaled iloprost [17].…”
Section: Discussionmentioning
confidence: 99%
“…[30][31] Use of the endothelin A/B receptor antagonist bosentan currently is under investigation. Hoeper and associates showed the effectiveness of bosentan as monotherapy 32 and in combination with inhaled iloprost 33 for the treatment of POPH. Approximately 10% patients treated with bosentan develop hepatotoxicity due to intracellular bile salt accumulation.…”
Section: Discussionmentioning
confidence: 99%